1997
DOI: 10.1093/oxfordjournals.pcp.a029185
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Components Implicated in the Stationary Organization of the Actin Cytoskeleton in Mesophyll Cells of Vallisneria

Abstract: In mesophyll cells of Vallisneria gigantea Graebner, an aquatic angiosperm, the association of the plasma membrane with the cell wall at the end wall has been reported to be indispensable for the mechanism that maintains the stationary organization of the bundles of microfilaments (MFs) [Masuda et al. (1991) Protoplasma 162: 151]. To identify putative extracellular components that might play a crucial role in this mechanism, we examined the effects of two exogenously applied synthetic hexapeptides, GRGDSP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In the work reported here, we inquired into the role of the cell wall-plasmalemma-cytoskeleton assembly, in the blue-light-induced movements of chloroplasts. In animal cells, the continuum between extracellular matrix, plasma membrane and cytoskeleton has a significant role in the perception of environmental signals leading to changes of development and motility (Ingber 1991, Masuda et al 1991, Edelman, 1993, Ryu et al 1997. Although recent evidence showed that in plant and animal cells the continuum may function in a similar way (Wagner et al 1992, Zhu et al 1993), significant differences exist between these two systems (Rezau & Point-Lezica 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In the work reported here, we inquired into the role of the cell wall-plasmalemma-cytoskeleton assembly, in the blue-light-induced movements of chloroplasts. In animal cells, the continuum between extracellular matrix, plasma membrane and cytoskeleton has a significant role in the perception of environmental signals leading to changes of development and motility (Ingber 1991, Masuda et al 1991, Edelman, 1993, Ryu et al 1997. Although recent evidence showed that in plant and animal cells the continuum may function in a similar way (Wagner et al 1992, Zhu et al 1993), significant differences exist between these two systems (Rezau & Point-Lezica 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is reinforced by the fact that RGD peptide acts on the microtubule network like plasmolysis does. Such relationships between cytoskeleton and ECM have been reported by Ryu et al (1997), and Zandomeni (1994) enlightening their role in mechanosensory reactions, More precisely Shibaoka (1993) provided evidence that, in tobacco BY2 cells, cortical microtubules are stabilized by binding to extracellular proteins like extensin, via transmembrane proteins. In our system there are no indications about the molecular nature of the agarose binding sites, but, as indicated by the RGD peptide effect, the connections of the agarose matrix with transmembrane proteins could stabilize the cortical microtubules.…”
Section: Discussionmentioning
confidence: 60%
“…In Vallisneria, it has been reported that association of plasma membrane with the cell wall is indispensable for the maintenance of organization of actin filaments (Masuda et al 1991). Involvement of extracellular protein was suggested (Ryu et al 1997). Thus, it is reasonable to speculate that transmission of extracellular signal through both the cell wall and the plasma membrane is involved in formation of rosette-shaped rhizoid in Spirogyra.…”
Section: Discussionmentioning
confidence: 99%